Construction of the Mortality Table with Gompertz's Law Using the 2019 TMI Reference - Janna, Nur; Tri Ayu Mulyani; Monica Dwi Kusumaningsih; Nur Amel Fitriyan; Agung Prabowo; Yaza Azzahara Ulyana (International Journal of Mathematics, Statistics, and Computing, 2023)
The Indonesian Mortality Table, which was specifically based on the real conditions of Indonesia, was successfully created for the first time in 1993. The mortality table was called the Indonesian Mortality Table (IMT) I of 1993. In its preparation from IMT II to IMT III, the time span was long enough that the Asosiasi Asuransi Jiwa Indonesia (AAJI) and Persatuan Aktuaris Indonesia (PAI) formed a team to prepare the Indonesian Mortality Table IV (IMT IV) which studied data during the study period between 2013-2017. Finally, the IV Indonesian Mortality Table was compiled in 2019. In this study, the mortality table used was the 2019 Indonesian Mortality Table issued by Persatuan Aktuaris Indonesia (PAI), as well as a modification of the 2019 IMT with Gompertz Law. In Gompertz's Law, one method that can be used is the least power square method. This study will show the suitability of Gompertz's Law against TMI 2019 for men and TMI 2019 for women, as well as to determine the suitability of Gompertz's Law using the Least Square Method for IMT 2019 for men and IMT 2019 for women.